PEMBERDAYAAN EKONOMI SYARI’AH DI LEMBAGA PENDIDIKAN DAKWAH (LPD) AL-BAHJAH CIREBON DAN KONTRIBUSINYA TERHADAP KESEJAHTERAAN MASYARAKAT - Inayatun Nisa; Aan Jaelani; Syafrudin Syafrudin (UIN Siber Syekh Nurjati Cirebon, 2021)
ABSTRACTThe results of this study indicate that the forms of Islamic economic empowerment in LPD Al-Bahjah further develop businesses in the field of goods and services which include business units Al-Bahjah Tour & Travel, BMT Al-Bahjah, AB Mart, Al-Bahjah Laundry, and AB Chicken. The supporting factors for economic empowerment in the LPD Al-Bahjah are the charismatic Kiai figure, sustainable human resource empowerment, neat interdisciplinary cooperation, the existence of permanent and clear consumers, and adequate business capital. Meanwhile, the factors hampering it were inadequate human resources and inadequate business unit locations. However, the empowerment of Islamic economics in LPD Al-Bahjah can be used as a role model for economic empowerment in other Islamic boarding schools. Keywords: Economic Empowerment; Islamic Boarding School; LPD Al-Bahjah.ABSTRAK Hasil penelitian ini menunjukkan bahwa bentuk-bentuk pemberdayaan ekonomi syariah di LPD Al-Bahjah lebih mengembangkan usaha bisnis dalam bidang barang dan jasa yang meliputi unit usaha Al-Bahjah Tour & Travel, BMT Al-Bahjah, AB Mart, Al-Bahjah Laundry, dan AB Chicken. Adapun faktor pendukung pemberdayaan ekonomi di LPD Al-Bahjah adalah adanya figur Kiai yang kharismatik, pemberdayaan SDM yang berkelanjutan, kerjasama antar divisi yang apik, adanya konsumen yang tetap dan jelas, serta modal usaha yang memadai. Sementara itu, faktor yang menghambatnya adalah SDM yang belum mencukupi dan tempat unit usaha yang kurang memadai. Namun demikian, pemberdayaan ekonomi syariah di LPD Al-Bahjah ini dapat dijadikan role model bagi pemberdayaan ekonomi di pondok pesantren lainnya. Kata Kunci: Pemberdayaan Ekonomi; Pondok Pesantren; LPD Al-Bahjah.